Youth in conflict with the law: a case study of critical issues that arise in sentencing youth who are on the verge of adulthood - Mablane, Kearabetswe (Department of Public Law, 2024)
Crime among youth in South Africa is a very serious and complex problem because it encompasses a lot of social issues that are deeply rooted. These issues encompass but are not limited to poverty, unemployment, disorganised families and communities, association with deviant peers, easy accessibility to illicit substances and poor education. As can be seen from statistics on youth who violate the law the amount of offences committed by young children is alarming negatively. Young children aged between 12 and 21 years are still forming part of the "high risk" for violating the law. As will be seen in the case in this study children are now becoming involved in heinous crimes. As alluded to above there are various factors that could have contributed to these children violating the law. These factors are called socio-economic risk factors. A great deal of children are already negatively affected by these risk factors. They come from poverty-stricken communities where unemployment is at its high and there is little to no adherence to the law. This is not only in the communities they come from but also in the homes that they live in. The school drop-out rate is very high and illicit substances are easily accessible to the youth. The peers they associate themselves with also contribute as they are most likely also deviant. That being the case, the number of children involved in crimes increases rapidly. Resources that are meant to cater for the needs of these children are fast becoming depleted because of overcrowding and other lack of resources. The lack of resources negatively affects these children because they often find it challenging to transition into responsible adults in most cases ending in recidivists and not contributing positively to the economy and society. This study explores a case of a young man from the Western Cape who has committed a very heinous crime. The case of the young man is then applied to the socio-criminogenic risk factors within the family, community, peer group association and school, in order to better understand the challenges that this young man might have (which are not unique to only him) the age that he is about to transition to being an adult. The study concludes that further in-depth research pertaining to youth who are about to transition into adulthood needs to be conducted. Research on the socio-criminogenic risk factors for youth who commit heinous crimes in the South African context is critical as the research will better guide the relevant stakeholders on where to focus much attention and emphases regarding rehabilitation and prevention of crime. Lastly, the sentences that youth are granted should be cognisant of the age when they committed the crime and the severity of their sentences should be less compared to those of adults.